2020
DOI: 10.1186/s42358-020-00145-5
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of methotrexate intolerance in longstanding rheumatoid arthritis: using the methotrexate intolerance severity score (MISS)

Abstract: Background: Methotrexate (MTX) intolerance is frequent, and its early identification may impact treatment, leading to timely changes in medication that may promote patient compliance and better control of rheumatoid arthritis (RA). The objective of this study was to identify the frequency of, and risk factors for, MTX intolerance using the Brazilian Portuguese version of the Methotrexate Intolerance Severity Score (MISS) questionnaire in patients with RA. Methods: This cross-sectional study was performed betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 24 publications
4
17
0
Order By: Relevance
“…Similar to other studies, gastrointestinal complaints like nausea were the most common in our study. In our study, MTX intolerance was associated with a younger age which has also been shown by previous studies 9,21,29 . Previously, some studies in juvenile idiopathic arthritis have found parenteral use to be associated with both higher and lower occurrence of intolerance 11,30 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to other studies, gastrointestinal complaints like nausea were the most common in our study. In our study, MTX intolerance was associated with a younger age which has also been shown by previous studies 9,21,29 . Previously, some studies in juvenile idiopathic arthritis have found parenteral use to be associated with both higher and lower occurrence of intolerance 11,30 .…”
Section: Discussionsupporting
confidence: 89%
“…In our study, MTX intolerance was associated with a younger age which has also been shown by previous studies. 9,21,29 Previously, some studies in juvenile idiopathic arthritis have found parenteral use to be associated with both higher and lower occurrence of intolerance. 11,30 However, we did not find any such association, perhaps due to a smaller proportion of patients on parenteral MTX in this study.…”
Section: Questionsmentioning
confidence: 99%
“…When multiple medications are prescribed, the risk of medication interactions increases along with the risk of AEs [ 28 ]. One study saw that when MTX was combined with frequent corticosteroid use, tolerance to MTX dropped significantly (odds ratio = 2.73; 95% confidence interval, 1.06 to 7.06; p = 0.038) [ 29 ]. When AEs become too severe or frequent, the patient-perceived risk-benefit declines leading to skipped doses or abandonment of the medication altogether [ 5 , 29 ].…”
Section: Reviewmentioning
confidence: 99%
“…One study saw that when MTX was combined with frequent corticosteroid use, tolerance to MTX dropped significantly (odds ratio = 2.73; 95% confidence interval, 1.06 to 7.06; p = 0.038) [ 29 ]. When AEs become too severe or frequent, the patient-perceived risk-benefit declines leading to skipped doses or abandonment of the medication altogether [ 5 , 29 ]. Even chronic fatigue, a common AE reported from those on multi-pharmacologic treatment regimen, was reported to cause such a detrimental emotional impact that eventually lead to nonadherence [ 5 , 28 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation